Genetic diversity of the major Dengue vectors Aedes aegypti and Aedes albopictus based on mitochondrial COI gene (Dhaka University Journal of Biological Sciences, 2025)
Dengue fever has emerged as a significant public health crisis in Bangladesh transmitted by Aedes mosquitoes. With a sharp rise in cases and fatalities, it poses a serious health risk to the communities. An authentic identification of major species of dengue vector is an utmost necessity for the control of dengue endemic. This study aims to understand molecular characterization and phylogenetic relationship of the key dengue vector mosquitoes. Specimens were collected from the wild habitat of Dhaka city and identified through morphological and molecular approaches. The Cytochrome c oxidase subunit I (COI) genes were amplified from the extracted genomic DNA by polymerase chain reaction using a pair of universal primers. The target nucleotide sequences of COI gene of collected mosquitoes were confirmed two species viz. Aedes aegypti and Ae. albopictus. Both species exhibit an A+T bias, with A+T content significantly higher (65.82% and 66.89%, respectively) compared to G+C content (34.18% and 33.11%, respectively). The genetic distance between the two species was found as 10.7. In the multiple sequence alignment, a total of 73 polymorphic sites were identified which can be distinguished from one another. Comparative analysis found moderate to high evolutionary divergence among the species from five different continents. Maximum likelihood tree indicates that members of Ae. aegypti and Ae. albopictus formed two separate clusters that supports our findings in evolutionary divergence. Further research needed on the remaining Dengue vector mosquitoes’ phylogeny, comparative genomic analysis and innovative vector control strategies.Dhaka Univ. J. Biol. Sci. 34(2): 29-39, 2025 (July)